Fundamental principles for the formation of the newest historical policy in the context of the escalation of the Russian-Ukrainian war - Nazarchuk, Oleksandr; Halytska-Didukh, Tamara; Horielov, Volodymyr; Krasnodemska, Iryna; Babichev, Oleksandr (Amazonia Investiga, 2023)
The Russian aggression against Ukraine and its historical accompaniment (which is used for propaganda) made the question of the answer relevant. The purpose of the article is to analyze the fundamental principles for the formation of the latest historical policy in the context of the escalation of the Russian-Ukrainian war. To implement this task, general scientific and special historical research methods were used (content analysis, prognostic method, comparative, typological, and systemic methods. The results considered the development of historical policy in Ukraine until 2022 and the main aspects of the formation of the current situation of this field and its future prospects. It was determined that at the state level, the Ukrainian Institute of National Memory forms the policy of memory. Young Ukrainian historical policy, however, has always been under the pressure of Russian influence, which directed a part of society against the decommunization and de-Sovietization of the historical past. In the future, it is important to review the existence of former Soviet institutions and their socio-cultural activities. An important stage is the official registration of decolonization processes at the legislative level. The conclusions draw attention to the importance of not only contemporary events getting into Ukrainian historical politics.